From WWI to www. – Put into the right place - Bajrektarevic, Anis H. (2014)
On 28th July exactly 100 years ago, Central Europe declared a war to Eastern Europe, an event that marked the official outbreak of World War I. This was a turning point which finally fractured a fragile equilibrium of La Belle Èpoque, and set the Old Continent and the whole world with it into the series of motions that lasted for almost a century, before docking us to our post-modern societies. From WWI to www.Too smooth and too good to be true? Let us use this occasion and briefly examine our post-modernity and some fallacies surrounding it.